The return of the king [compact disc, unabridged] - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973; Mayes, Bernard (Tolkien, J. R. R. (John Ronald Reuel), 1892-1973. Lord of the rings (HighBridge Audio (Firm)), 2002)
The original American full dramatization as broadcast on National Public Radio. War rages in the west, a titanic battle of will and strategy between the great wizard Gandalf and Sauron, the dark lord. Meanwhile, eastward in Mordor, Frodo and Sam approach the end of their improbable quest, bearing the One Ring ever closer to the Cracks of Doom, and to a final confrontation with the very essence of evil.